Antibody Drugs in Alzheimer’s Disease - Zhou, Jinghan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Alzheimer's disease is one of the important causes of Alzheimer's disease. The prevalence rate has been increasing in recent years, which is a hot issue for the medical community. In view of the pathogenesis of Alzheimer's disease is still not exactly diagnosed, the research and development of related drugs is not particularly ideal. Existing drugs mostly stay in symptomatic treatment. However, in recent years, the medical community has gradually turned to causative treatment. Among them, disease-modifying therapy (DMT) is the most frequently studied drug at present, accounting for 82.5% of the total drugs under consideration. Among the DMT-class drugs, 16 (equivalent to 15.4%) are specifically designed as anti-amyloid beta (Aβ) monoclonal antibodies (Mabs), while 11 (accounting for 10.6%) target tau proteins with monoclonal antibody technology.  Through reviewing past literature and comparing data, this paper takes Aducanumab, Lecanemab, and CCTM2 as examples to explore the therapeutic principles and make a summary.